2011
DOI: 10.1007/s10499-011-9427-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stocking density and type of feed on the rearing of crucian carp, Carassius carassius (L.), larvae under controlled conditions

Abstract: Two experiments were conducted into the rearing of crucian carp larvae under controlled conditions in an experimental closed water system. In both cases, the rearing lasted 21 days. The first experiment concerned the initial stocking density (from 50 to 600 individuals per l), whilst the second one studied the first food offered (two types of Artemia nauplii, decapsulated Artemia cysts and three types of commercial feeds) which were applied at the moment of exogenous feeding commencement. The best results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…These results are highly congruent with the findings of other researchers who concluded that many cyprinid larvae are sensitive to feeding with commercial dry food (Wolnicki and Górny, 1995a, 1995b, 1995cKaiser et al, 2003;Żarski et al, 2011). When only dry food was provided, crucian carp larvae grew very poorly and their mean body mass was only 7.3-8.8% at the end of 21 days long rearing experiments compared to the control groups fed with Artemia nauplii.…”
Section: Discussionsupporting
confidence: 90%
“…These results are highly congruent with the findings of other researchers who concluded that many cyprinid larvae are sensitive to feeding with commercial dry food (Wolnicki and Górny, 1995a, 1995b, 1995cKaiser et al, 2003;Żarski et al, 2011). When only dry food was provided, crucian carp larvae grew very poorly and their mean body mass was only 7.3-8.8% at the end of 21 days long rearing experiments compared to the control groups fed with Artemia nauplii.…”
Section: Discussionsupporting
confidence: 90%
“…This shows the importance of live food in many freshwater species during their initial period of exogenous feeding. This includes crucian carp (Żarski et al., ; Demény et al., ). However, larvae of the ide Leuciscus idus , the asp Aspius aspius and the rudd Scardinius erythophtalmus , are able to digest compound feed as early as 10 days post‐hatch feeding with Artemia (Kwiatkowski et al., ; Wolnicki et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the groups in which the feed type was switched gradually to compound feed, the tanks were cleaned three times a day (each time 15 minutes after the end of feeding). Feeding lasted 1 h with the dose given to the larvae in small portions every few minutes (as described by Żarski et al., ; Nowosad et al., ). Fifteen minutes after the feeding was completed, the excess feed was removed (Nowosad et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations